OPTIMIZATION OF USER-GENERATED CONTENT AS A DIGITAL MARKETING STRATEGY FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN SUNGAI PENUH CITY - Budaya, Indra; Santoni, Alvia; Sudirman (Journal of Business Studies and Management Review, 2026)
This study examines the optimization of User Generated Content (UGC) as a digital marketing strategy for Small and Medium Enterprises (SMEs) in Sungai Penuh City, Indonesia. Using quantitative analysis of secondary data from e-commerce platforms, including 1,250 consumer reviews and interaction data, this research evaluates the relationship between UGC engagement and consumer purchasing decisions. Sentiment analysis reveals that 78% of UGC related to local SMEs carries positive sentiment, while Structural Equation Modeling demonstrates significant relationships between UGC exposure, consumer trust (β=0.67, p<0.001), and purchase intention (β=0.58, p<0.001). The findings suggest that strategic UGC implementation can substantially enhance brand awareness and customer loyalty for regional SMEs with limited marketing resources. This study contributes to the growing literature on digital marketing strategies in emerging economies and provides practical recommendations for SME stakeholders in similar regional markets.